Estudio y diseño del tramo de acceso de la vía Laurel del recinto Yurima, del cantón Daule, para determinar el costo beneficio del proyecto - Cantos Chacón, Alejandro Xavier (2018)
The following thesis identifies the project as “Study and design of the access stretch of the Lauren road of the Yurima precinct, of the canton Daule, belonging to the province of Guayas”, is easy to detect the needs of the inhabitants of said precinct, due to the fact that the production is not easily mobilized to the consumption zones. However, in the case of an emergency the access of emergency services is hindered, therefore this project will offer the community an access route according to the inhabitants needs, contributing in some way to the growth of the economy and the country’s road infrastructure……..